Conversion of a non-selective adenosine receptor antagonist into A3-selective high affinity fluorescent probes using peptide-based linkers - Vernall, Andrea J.; Stoddart, Leigh A.; Briddon, Stephen J.; Ng, Hui Wen; Laughton, Charles A.; Doughty, Stephen W.; Hill, Stephen J.; Kellam, Barrie (Royal Society of Chemistry, 2013)
Advances in fluorescence-based imaging technologies have helped propel the study of real-time biological readouts and analysis across many different areas. In particular the use of fluorescent ligands as chemical tools to study proteins such as G protein-coupled receptors (GPCRs) has received ongoing interest. Methods to improve the efficient chemical synthesis of fluorescent ligands remain of paramount importance to ensure this area of bioanalysis continues to advance. Here we report conversion of the non-selective GPCR adenosine receptor antagonist Xanthine Amine Congener into higher affinity and more receptor subtype-selective fluorescent antagonists. This was achieved through insertion and optimisation of a dipeptide linker between the adenosine receptor pharmacophore and the fluorophore. Fluorescent probe 27 containing BODIPY 630/650 (pKD = 9.12 ± 0.05 [hA3AR]), and BODIPY FL-containing 28 (pKD = 7.96 ± 0.09 [hA3AR]) demonstrated clear, displaceable membrane binding using fluorescent confocal microscopy. From in silico analysis of the docked ligand-receptor complexes of 27, we suggest regions of molecular interaction that could account for the observed selectivity of these peptide-linker based fluorescent conjugates. This general approach of converting a non-selective ligand to a selective biological tool could be applied to other ligands of interest.